식이유도 비만 흰쥐에서 루와이 위우회술이 체중, 그렐린 및 PYY3-36에 미치는 영향 - 이상권(Sang Kuon Lee); 정헌(Hun Jung); 전해명(Hae Myung Jeon); 김응국(Eung Kook Kim) (Annals of surgical treatment and research, 2010)
Purpose: Obesity is considered an epidemic worldwide. Nonsurgical treatment such as dietary, physical and pharmacological therapies have limited success and thus, bariatric surgery is the ultimate option. Roux-en-Y gastric bypass (RYGB) is a bariatric procedure, which is a restrictive and malabsorptive procedure simultaneously. The purpose of this study was to develop surgical rat models of bariatric surgery and analyze the effect of gastric bypass on body weight, ghrelin and polypeptide YY3-36 (PYY3-36) changes in rats. Methods: RYGB, sleeve gastrectomy (SG) and sham operation were performed in diet-induced obese rats and compared to obese control and normal control rats. Results: In RYGB group, 20.7±8.56% of weight loss was achieved on postoperative day 18 and maintained thereafter. This outcome was significant compared to SG (8.8±1.82%) and sham operated (6.2±2.45%) groups. When pre- and postoperative ghrelin levels were compared, there was a significant decrease in RYGB group (P＜ 0.028); nonetheless, there was no difference in SG and sham operated groups. When pre- and postoperative PYY3-36 levels were compared, there was a significant increase in RYGB (P＜0.028), SG (P＜0.031) and sham operated (P＜0.031) groups. Conclusion: We developed surgical rat models of RYGB and SG. Those rats that underwent RYGB lost significant body weight and maintained the weight thereafter. The decrease in ghrelin and increase in PYY3-36 may be associated with loss of appetite and delay in intestinal transit time with subsequent weight loss maintenance. In the future, this rat model would serve as a tool for further study on endocrine regulation of obesity. Purpose: Obesity is considered an epidemic worldwide. Nonsurgical treatment such as dietary, physical and pharmacological therapies have limited success and thus, bariatric surgery is the ultimate option. Roux-en-Y gastric bypass (RYGB) is a bariatric procedure, which is a restrictive and malabsorptive procedure simultaneously. The purpose of this study was to develop surgical rat models of bariatric surgery and analyze the effect of gastric bypass on body weight, ghrelin and polypeptide YY3-36 (PYY3-36) changes in rats. Methods: RYGB, sleeve gastrectomy (SG) and sham operation were performed in diet-induced obese rats and compared to obese control and normal control rats. Results: In RYGB group, 20.7±8.56% of weight loss was achieved on postoperative day 18 and maintained thereafter. This outcome was significant compared to SG (8.8±1.82%) and sham operated (6.2±2.45%) groups. When pre- and postoperative ghrelin levels were compared, there was a significant decrease in RYGB group (P＜ 0.028); nonetheless, there was no difference in SG and sham operated groups. When pre- and postoperative PYY3-36 levels were compared, there was a significant increase in RYGB (P＜0.028), SG (P＜0.031) and sham operated (P＜0.031) groups. Conclusion: We developed surgical rat models of RYGB and SG. Those rats that underwent RYGB lost significant body weight and maintained the weight thereafter. The decrease in ghrelin and increase in PYY3-36 may be associated with loss of appetite and delay in intestinal transit time with subsequent weight loss maintenance. In the future, this rat model would serve as a tool for further study on endocrine regulation of obesity. KCI Citation Count: 0